Mineral composition and ratios in aortic valves, serum, and epicardial fat among patients with aortic stenosis undergoing aortic valve replacement - Barbara Poniedziałek; Bartłomiej Perek; Aleksandra Proch; Anna Komosa; Przemysław Niedzielski; Piotr Buczkowski; Marek Jemielity; Piotr Rzymski (Scientific Reports)
Abstract Aortic stenosis (AS) is a leading cause of surgical intervention in adults with acquired heart disease, driven by an aging population and advancements in diagnostic and treatment approaches. This study aimed to investigate levels of macroelements (Ca, K, Na, Mg, and P) in aortic valve tissues, serum, and epicardial fat in patients undergoing aortic valve replacement due to degenerative disease. Elemental composition was determined using inductively coupled plasma mass spectrometry. Analyses revealed a distinct accumulation of Ca and P in aortic valve tissues, not correlated to and exceeding that in epicardial adipose tissue, suggesting localized mineralization. Significant relationships between serum and aortic valve element concentrations were found, with serum K and Mg levels inversely correlated with Ca and P deposition and Ca/P ratio in the valve, highlighting their potential role as calcification inhibitors. Moreover, serum and valvular Na/K ratios were positively correlated. Furthermore, patient age was associated with increased Ca, Mg, Na, P levels, and Ca/P ratio in valve tissues, reinforcing age as a risk factor for valvular calcification. Creatinine and lipoprotein (a) levels correlated positively with valvular K content and Ca/P ratio, respectively, while high-density lipoprotein cholesterol concentration was positively associated with Ca, Mg, and P content in epicardial fat. Patients with increased transvalvular systolic pressure gradient revealed higher valvular Na content. Future longitudinal research should address mineralization across earlier disease stages, exploring additional trace elements and molecular contributors to advance understanding of calcification mechanisms, ultimately aiding in developing biomarkers or therapeutic strategies for postponing or preventing AS onset.